Clinical classification and individualized design for the treatment of basicranial artery injuries. Issue 11 (March 2019) - Yang, Hua; Li, Sheng-Gang; Xiang, Xin; Lv, Ying; Chu, Liang-Zhao; Peng, Han; Wang, Fan; Cao, Han; Liu, Jian
Abstract : Abstract: This study aims to explore the principles of clinical classification and individualized treatment of basicranial artery injuries based on its anatomical correlation. The data of 172 patients with various types of basicranial artery injuries were retrospectively analyzed. Among these patients, 128 patients were male and 44 patients were female, and the average age of these patients was 28.3 years old. All patients underwent computed tomography, some patients underwent computed tomography angiography or magnetic resonance angiography, and all the diagnoses were confirmed by digital subtraction angiography (DSA). According to anatomical correlation, the injuries were classified into 5 types: vascular wall injury (type I), intradural injury (type II), epidural injury (type III), sinus injury (type IV), and skull base bone injury (type V). Individualized treatment was adopted based on the different types and characteristics of injuries. The percentages of basicranial artery injuries were as follows: type I, 4.6%; type II, 5.8%; type III, 3.5%; type IV, 77.9%; and type V, 8.1%. All 172 patients underwent DSA to demonstrate the classification. The lesion elimination rate revealed by DSA was 99.4% immediately after the operation, 98.3% at 1 week after the operation, and 98.8% at 3 months after the operation. The follow-up after 6 months revealed that the percentage of patients in whom clinical symptoms or signs completely disappeared was 97.7%, the percentage of patients with limited eye movement or visual impairment was 1.2%, and the percentage of patients with mild limb dysfunction was 0.6%. Basicranial artery injuries can be classified into 5 types. Individualized design of embolization therapy based on different characteristics might be applicable for basicranial artery injuries treatment.